Potencialidades turísticas de los recursos naturales de la ciudad de Babahoyo - Paredes Guachambosa, Paola Michel (2020)
The objective of this case study is to assess the natural resources of the city of Babahoyo, determining their potential to be used at the tourist level, hierarchical ranges were established taken from the Methodological Guide for the Hierarchization of Attractions and Generation of Tourist Spaces of Ecuador (MINTUR 2017) where it was determined that the Cerro Cacharí and the Babahoyo River are considered resources. The methodology used to carry out this case study was given through descriptive research and field observation to carry out the information survey sheet with the aim of evaluating the natural resources found in Babahoyo, the Technique of interviews with officials of the Municipality of Babahoyo and the Department of Tourism, in order to gather truthful information on the current situation in which the natural resources of Babahoyo are found and what will be the use of the tourist potential that influences the increase visitors. In the main results obtained, it was identified that the resources do not have tourist facilities or security measures, while the Babahoyo River is a resource that is complemented by other attractions to take advantage of its potential, however, the river has high levels of contamination , a situation that disadvantages the city and tourism.